UPAYA PEMBINAAN KEPRIBADIAN DAN KEMANDIRIAN SANTRI DALAM PELAYANAN KESEJAHTERAAN SANTRI (Studi di Pondok Pesantren Tahfidz Baitul Qur’an Kendari) - Yanti, Eka Saputri; Bauto, La Ode Monto; Tawulo, Megawati Asrul (Universitas Halu Oleo, 2020)
This study aims to (1) To find out the efforts made by the Islamic Boarding School Tahfidz Baitul Qur'an Kendari in fostering personality and independence to students (2) To find out the welfare system of students provided by the Islamic Boarding School Tahfidz Baitul Qur'an Kendari to students (3 ) To find out the supporting and inhibiting factors in fostering personality and independence to students.This research was conducted at the Islamic Boarding School Tahfidz Baitul Qur'an Kendari located at Jalan Wua Eha, Anggoeya Village, Poasia District. Analysis of the data used is qualitative analysis while data sources use primary data and secondary data. Data collection techniques in this study used observation, interview, and documentation techniques. The results of this study indicate the efforts made by the Islamic Boarding School Tahfidz Baitul Qur'an kendari in fostering the Personality and Self-Reliance of Santri, namely by providing moral guidance, religious guidance, memorizing the Qur'an, fostering religious education, entrepreneurship management of shops, shops, making food. And Hadroh Art Skills. Santri Welfare Services System in fostering the Personality and Independence of Santri by providing Servicing Services, Educational Scholarship Services, and Health Services. The supporting and inhibiting factors in fostering the personality and independence of students are supporting factors including Community Concern, adequate Facilities and Infrastructure, and Location of the Baitf Qurzan Islamic Boarding School Baitul Qur'an in a strategic vehicle. In addition, the inhibiting factor was also felt by the Tahfidz Baitul Qur'an Islamic Boarding School in kendari, such as the Irregular Donors.